PENGARUH CUSTOMER RELATIONSHIP MANAGEMANT (CRM), SERVICE QUALITY, DAN PRODUCT AVAILABILITY DALAM MEMBANGUN LOYALITAS PELANGGAN DENGAN KEPUASAN PELANGGAN SEBAGAI MEDIASI PADA TOKO GROSIR UD. KARUNIA SITUBONDO - Mohammad Iqbal Nur Azizi; Randika Fandiyanto; Riska Ayu Pramesthi (Fakultas Ekonomi dan Bisnis, 2026)
Wholesale stores play a role as a driving force for the local economy by maintaining affordable food prices for the general public. Wholesale stores remain a primary choice because they offer lower prices, a complete inventory, and ease of shopping for consumers. The purpose of this study is to analyze and test the influence of customer relationship management, service quality, and product availability on customer loyalty through customer satisfaction as a mediator at UD. Karunia Situbondo Wholesale Store. The sampling technique used non-probability sampling. Data analysis and hypothesis testing in this study used the Structural Equation Model-Partial Least Squares (PLS-SEM). The results of the direct effect hypothesis test using the Smart PLS 3.0 application indicate that CRM has a significant negative effect on customer satisfaction, service quality has a significant positive effect on customer satisfaction, product availability has a significant positive effect on customer satisfaction, CRM has a significant positive effect on customer loyalty, service quality has a positive but insignificant effect on customer loyalty, product availability has a significant positive effect on customer loyalty, and customer satisfaction has a positive but insignificant effect on customer loyalty. The results of the indirect effect hypothesis test indicate that CRM has a negative and insignificant effect on customer loyalty through customer satisfaction, service quality has a positive but insignificant effect on customer loyalty through customer satisfaction, and product availability has a positive but insignificant effect on customer loyalty through customer satisfaction.